2016
DOI: 10.5935/0004-2749.20160092
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of contrast sensitivity testing in patients with age-related macular degeneration, glaucoma, and cataract

Abstract: Approved by the following research ethics committee: Canakkale Onsekiz Mart University (#050. 99-151). ABSTRACTPurpose: To analyze the intrasession and intersession repeatability of contrast sensitivity (CS) measurements in patients with glaucoma, cataract, or age-related macular degeneration (AMD) and healthy controls. Methods: CS measurements were performed using the OPTEC-Functional Vision Analyzer (FVA), which uses a standardized and closed (view-in) system. Measurements for patients with glaucoma, catarac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Visual assessments performed at the clinic comparing baseline (pre-treatment) and week 7 (post-treatment) demonstrated an enhanced CS in both left ( Oculus Sinister , OS) and right ( Oculus Dexter , OD) eyes. CS improved at 2 cyc/deg from 1.65 to 2.1 logits [COR ±0.24 logits ( 30 )] in OS ( Figure 3A ). CS increased at 0.5, 2, and 6 cyc/deg for OD from 1.54 to 1.85 logits, from 1.85 to 2.1 logits, and from 1.6 to 1.95 logits [COR ±0.24 logits ( 30 )], respectively ( Figure 3A ).…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual assessments performed at the clinic comparing baseline (pre-treatment) and week 7 (post-treatment) demonstrated an enhanced CS in both left ( Oculus Sinister , OS) and right ( Oculus Dexter , OD) eyes. CS improved at 2 cyc/deg from 1.65 to 2.1 logits [COR ±0.24 logits ( 30 )] in OS ( Figure 3A ). CS increased at 0.5, 2, and 6 cyc/deg for OD from 1.54 to 1.85 logits, from 1.85 to 2.1 logits, and from 1.6 to 1.95 logits [COR ±0.24 logits ( 30 )], respectively ( Figure 3A ).…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
“…CS improved at 2 cyc/deg from 1.65 to 2.1 logits [COR ±0.24 logits ( 30 )] in OS ( Figure 3A ). CS increased at 0.5, 2, and 6 cyc/deg for OD from 1.54 to 1.85 logits, from 1.85 to 2.1 logits, and from 1.6 to 1.95 logits [COR ±0.24 logits ( 30 )], respectively ( Figure 3A ). Visual field analysis revealed that the number of points seen in the binocular Esterman field of vision test increased from 66 points seen at baseline to 69 at week 3 and 73 at week 7 with some reorganization (black circles indicate loss of points, red squares indicate acquired points, net change: +7 points, all in the blind left hemifield, +5.8% from baseline, Table 2 , Figure 3B ).…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The contrast sensitivity function (CSF) provides a comprehensive assessment of spatial vision at a variety of spatial frequencies, 1 and is used to evaluate and screen a variety of visual disorders. 2 8 The conventional CSF measurement in the laboratory is very time-consuming, 9 while the clinically available chart for CSF assessment, such as the Vistech chart or Functional Acuity Contrast Test (FACT) exhibited very poor test–retest reliability. 10 , 11 Recently, Lesmes et al 12 developed the Bayesian adaptive quick CSF (qCSF) method to efficiently measure the CSF with high precision and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Particularly, despite normal visual acuity, foveal contrast sensitivity was found to be significantly impaired even in early stages of glaucoma compared with normal cohorts. [12][13][14][15][16] Contrast sensitivity, the ability to detect differences in contrast, is a fundamental building block of human pattern vision, and thus affects a wide range of everyday visual functions, such as reading, [17][18][19] object/face recognition, 20,21 gait, 19,22 and driving 23,24 (also see a review 25 ). Contrast information (i.e., the intensity difference between the light and dark regions of visual space) is first encoded in center-surround RGCs 26 and further processed in the downstream cortical areas.…”
mentioning
confidence: 99%